THE EFFECT OF SALARY AND LOYALTY ON THE PERFORMANCE OF SETIBEL TUTORING TEACHERS IN MOJOSARI, MOJOKERTO REGENCY - Wulandari Dita; Is Fadhilah; Anis Fitriyasari (Suluh Adiluhung Publisher (SAPub), 2025)
This study aims to analyze the effect of salary and loyalty on the performance of Bimbel Setibel teachers in Mojosari, Mojokerto Regency. The research method used is quantitative with data collection through questionnaires distributed to Bimbel Setibel teachers. The results of the study are expected to provide information on how much influence the salary and loyalty of teachers have on their performance. Other studies show that the level of teacher income is positively correlated with teaching performance. Teacher loyalty also has a significant effect on performance. Adequate compensation can increase teacher work loyalty. Job satisfaction is needed to increase teacher loyalty and has a positive impact on improving performance. This study is expected to provide implications for Bimbel Setibel management in improving teacher performance through increasing salary and loyalty.